Religious Tolerance Measurement: Validity Test in Indonesia - Alfariz, Arif Budiman; Saloom, Gazi (FAKULTAS PSIKOLOGI UIN SYARIF HIDAYATULLAH JAKARTA, 2021)
This study aims to determine the construct validity of items in the religious tolerance scale constructed by Witenberg (2007). There are three aspects or dimensions of religious tolerance used in this scale: fairness, empathy, and reasonableness. This study examines the religious tolerance scale, particularly in Indonesia, using a psychological perspective. The sample is 360 students of Syarif Hidayatullah State Islamic University of Jakarta. The samples use non-probability sampling with a purposive sampling technique. This study uses Confirmatory Factor Analysis (CFA) method and analyzed by software Lisrel 8.7. The results show that the religious tolerance model has a model fit, and this scale is unidimensional. From 30 items, item 12 of the fairness dimension is not valid.